A Young Women With Infected Bronchiectasis and Paraseptal Emphysema - Mafisah, Saidah; Sugiri, Yani Jane; Sartono, Teguh Rahayu; Karliasari, Liana (Universitaas Brawijaya, 2025)
Introduction: Bronchiectasis is defined as an abnormal dilation of the bronchi, usually as a result of chronic airway inflammation and/or infection. Bronchiectasis with non-mycobacterial tuberculosis infection is more common in women. Paraseptal emphysema formed around the pleura or septa in the upper lobe, caused by repeated infections, smoking, or deficiency of the alpha 1 antitrypsin enzyme. Emphysema is more common in men with a history of smoking. Case: A 22 year-old female came with chief complaint of chronic cough. No smoking history. Patient had a history of repeated hospitalizations due to pneumonia. Fungal culture results with no fungal growth and sputum molecular rapid test result is mycobacterium tuberculosis not detected. Achromobacter denitrificans Multiple Drug Resistance was found through bronchial washings culture. Thorax Computed Tomography Scan showed cavities connected to the bronchi with air fluid level (infected bronchiectasis) and air space in upper lobes (paraseptal emphysema). Patient was given definitive antibiotic and clinically improved. Discussion: Bronchiectasis and paraseptal emphysema are caused recurrent lung infections. Bronchiectasis with non-mycobacterial tuberculosis infection is more common in women. In this case, we found infected bronchiectasis and paraseptal emphysema in a young women with no history of smoking but with a history of recurrent pneumonia. Conclusion: Possible causes of bronchiectasis and paraseptal emphysema in this patient was due to recurrent lung infection. The patient had been given definitive antibiotic treatment and clinically improve now. In addition, appropriate and adequate therapy are needed to reduce progression and complications of this disease.